Synthesis, characterization and ferromagnetic properties of Zn1-xMnxO (x ≤ 0.05) nanoparticles - Anukorn Phuruangrat (2018)
© 2018 Elsevier B.V. Zn 1-x Mn x O (x ≤ 0.05) nanoparticles were synthesized by a combination of room temperature precipitation and high temperature calcination. Pure hexagonal wurtzite ZnO nanoparticles with the size of ≤100 nm and a dominant vibrational peak at 437 cm −1 of E 2H non-polar optical phonon mode were detected. The present research was succeeded in doping of ZnO lattice by Mn 2+ ions, including the detection of an additional peak at 528 cm −1 associated with lattice defects. Magnetic properties of Zn 1-x Mn x O (x ≤ 0.05) nanoparticles were controlled by correlated spin of Mn–O–Mn exchange couple and lattice disorder. The saturation magnetization of ferromagnetic Zn 0.97 Mn 0.03 O was the highest at 51.49 × 10 −3 emu/g.